Modelling the effects of affordable housing 'sticks' and 'carrots' for developer-delivered projects. (2nd September 2019) - Warren-Myers, Georgia; McRae, Erryn; Raynor, Katrina; Palm, Matthew
ABSTRACT: The literature suggests both "Stick" and "Carrot" initiatives can encourage property developers to include Affordable Housing in their developments. Such initiatives include affordable housing contributions or requirements (the stick) and land cost subsidies, density bonuses, access to low-interest finance, reduced planning timeframes and reduced car parking requirements (the carrots). Despite their widespread application internationally, Australian developers and policymakers have resisted affordable housing incentive structures. Recent legislation in Victoria empowers local planners to approve affordable housing contributions and incentives on acase-by-case basis. This paper provides aquantitative study investigating the feasibility of introducing housing affordability contributions and incentives when developers enter the planning process. This paper demonstrates aone-size fits all approach to affordable housing contributions and incentives may not be appropriate, modelled through scenario analysis of three different sized case studies. Optimum scenarios identified a balance of carrots and sticks. However, project characteristics determined the applicability and effectiveness of an incentive for aproject. Therefore, asingular approach may not be appropriate for all projects in amunicipality or state; and alayered and flexible approach for "Sticks" and "Carrots" should be considered to maximise the social benefit of these incentives and ensure developers financial viability.